Ecocriticism : the essential reader - Hiltner, Ken (London Routledge, 2015)
"Ecocriticism: The Essential Reader charts the growth of this important field. The first-wave ecocriticism section focuses on key readings from the 1960s to the 1990s. The second-wave ecocriticism section goes on to consider a range of exciting contemporary trends, including environmental justice, aesthetics and philosophy, and globalization.Readings include the work of:Raymond WilliamsJonathan BateTimothy MortonUrsula HeiseLawrence BuellKate SoperCary Wolfeand Kate Rigby.Containing seminal, representative, and contemporary work in the field, this volume and the editorial commentary is designed for use on both undergraduate and postgraduate ecocritical literature courses"--
"Ecocriticism: The Essential Reader Ecocriticism: The Essential Reader charts the growth of this important field. The first-wave Ecocriticism section focuses on key readings from the 1960s to the 1990s. The second-wave Ecocriticism section goes on to consider a range of exciting contemporary trends, including environmental justice, aesthetics and philosophy, and globalization. Readings include the work of: - Raymond Williams - Jonathan Bate - Timothy Morton - Ursula Heise - Lawrence Buell - Kate Soper - Cary Wolfe - Kate Rigby. Containing seminal, representative, and contemporary work in the field, this volume and the editorial commentary is designed for use on both undergraduate and postgraduate ecocritical literature courses"--
Includes bibliographical references and index.
Keywords: Ecocriticism; Ecology in literature; Environmental protection in literature; LITERARY CRITICISM / General